If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 7 = 8x + -11 Reorder the terms: 7 + 10x = 8x + -11 Reorder the terms: 7 + 10x = -11 + 8x Solving 7 + 10x = -11 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 7 + 10x + -8x = -11 + 8x + -8x Combine like terms: 10x + -8x = 2x 7 + 2x = -11 + 8x + -8x Combine like terms: 8x + -8x = 0 7 + 2x = -11 + 0 7 + 2x = -11 Add '-7' to each side of the equation. 7 + -7 + 2x = -11 + -7 Combine like terms: 7 + -7 = 0 0 + 2x = -11 + -7 2x = -11 + -7 Combine like terms: -11 + -7 = -18 2x = -18 Divide each side by '2'. x = -9 Simplifying x = -9
| 6c^3-3c^2-45c=0 | | 3d^2-2d-33=0 | | 6n^2+1-n+5n^2= | | 2c-15=36 | | 2x+31=9x-53 | | -3a+a=3a-9 | | 3x+3=7x-41 | | 3(p+4)=21 | | X+20x=32 | | 2x-6x-23=0 | | 5(k+3)=25 | | 8y^2+9y-4=0 | | 6x-2x+6=36 | | 12x-5=7x+5 | | 3x+4=7x+8 | | y^4-y^2-72=0 | | 2p^2+5p=8 | | 7x-18=y+3 | | 11k+3=k+17 | | 7x-x=42 | | 7(y-3)=35 | | 2(3x-7)=2-10x | | -8=32-5x | | 2(4+x)=12 | | 9+7=29+5 | | 3x+12=2x-2 | | 6-7x=4(2x-6) | | 5y=10x+10 | | 6x+11=121-5x | | 8x^2-4x=24 | | 6x+2x=73.2 | | 8y=32 |